Development of executive function in typically-developing preschoolers in relation to motor skill development - Laufs, Ruth (2018)
Executive Function (EF) is an umbrella term for higher-order cognitive skills, which build the basis for goal-directed behavior. In general, three separable, yet interrelated components are assumed, Inhibition, Working Memory and Shifting. Because of their predictive power for many positive outcomes, they are regarded as crucial competences for coping with various aspects of everyday life. Recent research has found evidence for an interrelation between EF and motor skills. Since both EF and motor skills develop rapidly during early childhood, this age range is of particular interest for research. The dissertation at hand aimed at providing more evidence for (a) age-related increases regarding two “core” Executive Functions, Inhibition and Working Memory, and (b) their proposed interrelation with fine and gross motor skills, both cross-sectionally and longitudinally. The present research project was designed as a 3-year-longitudinal study with annual intervals. 170 normally-developing children between 3 and 6 years of age were tested at the first point of data collection. In the following two years, 109 and 60 children respectively participated again. At each interval, EF was assessed via performance-based tasks and parent ratings and motor skills were assessed via a standardized assessment battery. The analyses of the cross-sectional data collected at the first point of data collection provide further evidence for age-related increases in Inhibition and Working Memory. Furthermore, a Structural Equation Model showed significant interrelations between fine motor skills and both EF components, and substantial, albeit non-significant, correlations between gross motor skills and both domains of EF. The analysis of the longitudinal data stated a significant prediction of Inhibition via gross motor skills one year earlier. Although to a large part exploratory and hypotheses-generating, the results of the research project provide further evidence for an interrelation between EF and motor skills and give rise to the question, whether motor skills can be used in intervention studies aiming at the promotion of EF. However, due to the modicum of research regarding this topic in preschoolers, the results should be regarded first and foremost preliminary.
Key words: Executive Function, motor skills, preschool
Keywords: Hochschulschrift